Shifting the perspective from 'incapable' to 'capable' for artists with cognitive disability; case studies in Australia and South Korea. Issue 3 (16th March 2021) - Yoon, Jung Hyoung; Ellison, Caroline; Essl, Peggy
Abstract: This study examined four inclusive arts organisations in Australia and South Korea, providing creative services for artists living with cognitive disability, including autism, intellectual and mental disability. This research study focused on exploring what support inclusive arts organisations and society have provided for artists living with cognitive disability to pursue professional careers. The qualitative study used proxy intervention interviews with art staff and administrators from the four inclusive arts organisations and observation as a research method to include artists living with cognitive disability who do not speak. The findings reveal significant social support and strategies of the organisations are needed for artists living with cognitive disability to develop their art careers. It also discusses the impact of shifting the perception of disability from 'incapable' to 'capable' for artists living with cognitive disability in the wider mainstream art community and society. Points of interest: The study collected data through proxy interviews and observation in inclusive arts organisations which provide significant individual and organisational support for artists living with cognitive disability in Australia and South Korea The study found a growing demand for the development of artistic careers for artists living with cognitive disability as professionals beyond therapeutic or recreational art. Inclusive arts organisations provide creative services as a pathway of professional development for artists living with severe cognitive disability and communication difficulty. Art staff and administrators consulted in this study asserted that the public perception of people living with disability as being 'incapable' is embedded in our society. The study discusses positive ripple-effects on society when the perception around disability is shifted from 'incapable' to 'capable'.